Voces ciudadanas. Deliberation open to the ordinary citizen - Miralles Castellanos, Ana María (2006)
In this anide philosophical and methodological basis of public journalism will be presented through the project Voces Ciudadanas (Colombia) experience, a pioneer in Latin America. This will be done by means of an analysis ofVoces Ciudadanas expetience after five years work in the field of public journalism, with a philosophy of journalism which seriously  states the building of the public as a communication problem and a creator of the citizenship culture since the project included people in the deliberarion of the collective from a journalism pattern which is more communicative than informative